Investigating customer loyalty formation for wellness spa: Individualism vs. collectivism. (October 2017) - Han, Heesup; Kiatkawsin, Kiattipoom; Kim, Wansoo; Lee, Sanghyeop
Highlights: We examined wellness spa customers' destination loyalty formation. Moderating role of culture (individualism vs. collectivism) was identified. The importance of quality, value, affect, satisfaction, and desire in building loyalty was found. Abstract: Visitor retention is undeniably a major issue for every destination marketer. This study was an attempt to develop an international tourists' loyalty framework for wellness spa tourism destination by considering quality and value of spa tourism in Thailand, affect, satisfaction, desire, and culture. Our proposed framework and hypothesized relationships were evaluated by using a structural analysis. A field survey was used. Results indicated that our conceptual model included a satisfactory fit to the data. Quality and value were found to have a critical role, and other study constructs were identified to act as direct/indirect driving forces of loyalty intentions. In addition, mediating role of affect, satisfaction, and desire was found. Moreover, moderating impact of culture (individualism vs. collectivism) on the loyalty formation was identified. Overall, our theoretical framework was demonstrated to be capable of explicating wellness spa tourists' destination loyalty formation. Implications for destination marketers in Thailand are discussed.